The Effect of Applying Learning Together Method on the Students’ Reading Comprehension - Haryato Siregar; Elia Masa Ginting (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
This study was aimed at finding out the effect of applying Learning Together Method on the students’ reading comprehension. This study used the experimental design. The population of this study was the students of SMP Negeri 1 Muara. There were sixty students of eighth class as the sample of the research. This study was conducted with two randomized groups namely experimental and control group. The experimental group was taught by applying Learning Together Method while control group was taught without applying Learning Together Method. The instrument of collecting the data was multiple choice test which consists of 20 items. To obtain the reliability of the test, the researcher used Kuder-Richardson (KR-21) formula. The calculation shows the reliability was 0.82(high). The data were analyzed by using t-test. The calculation shows that t-observed (4.9) is higher than t-table (2.00) at the level of significance (α) 0.05 with the degree of freedom (df) 58. Therefore, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that teaching reading comprehension by applying Learning Together Method significantly affect reading comprehension. Keywords: Learning Together Method, Reading Comprehension